Analisis Vegetasi Sebagai Dasar Pengembangan Agroforestri di DAS Mikro Desa Tukad Sumaga, Kecamatan Gerokgak, Kabupaten Buleleng - WIRYANTARA, I WAYAN GEDE; WIJANA, GEDE; SUARNA, I WAYAN (Agrotrop : Journal on Agriculture Science; Vol 4 No 1 (2014), 2014)
Vegetations Analysis As A Basic ForAgroforestry Development In Micro Watershed TukadSumaga Village, Gerokgak District, Buleleng Regency. Forest changed to agricultural hasconsciousness can effected many problems such as soil degradations, erosion, flora and fauna extinctions,floods, dryness, and even global environmental change. Agroforestry is one of solutions to protect thebiodiversity. The research was held at Micro Watershed Tukad Sumaga Village, Gerokgak District,Buleleng Regency which consist of intercropping agroforestry system, alley cropping agroforestry system,and the trees for soil conservations agroforestry system. The purpose of this research is to discoverbiodiversity and composition of vegetations species in each agroforestry system and also to find out theagroforestry management level at Micro Watershed Tukad Sumaga Village. The research result showsthat the biggest Important Value Index (INP) in intercropping agroforestry system is in trees level bymango at 59.46%, scrubs and sapling level by teak at 80.13%, seddling level by gosh bean at 49.57%.The biggest INP in Alley Cropping Agroforestry System is in trees level by cashew at 150.33%, scrubsand saplings level by lamtoro at 95.26%, seedling level by legetan at 84,93%. The biggest INP in TheTrees for Soil Conservations Agroforestry System is in trees level by tamarind at 165,35%, %, scrubsand saplings level by india apple at 114.09%, seedling level by legetan at 83.98%. The calculations ofspecies biodiversity which as species variety, prevalent index, and domination index can separated themanagement level in each agroforestry system. The best management is Intercropping AgroforestrySystem. The second is The Trees for Soil Conservations Agroforestry System. The last is Alley CroppingAgroforestry System. The development of Intercropping Agroforestry System is needed because thissystem is the best. Monitoring, evaluations, and technical learning about forest and agricultural plantationare needed for increasing the social benefit dan preventing the deforestations.
Keywords: composition of vegetations species; biodiversity; level management of agroforestry